Prognostic implications of immune classification based on PD-L1 expression and tumor-infiltrating lymphocytes in endocervical adenocarcinoma - Li-Jun Wei; Zi-Yun Wu; Li-Yan Wu; Ying-Wen Wu; Hao-Yu Liang; Rong-Zhen Luo; Li-Li Liu (Translational Oncology)
Background: Endocervical adenocarcinoma (ECA) comprises a heterogeneous group of diseases whose incidence has increased significantly in recent decades. ECA can be histologically classified into human papillomavirus-associated (HPVA) and non-HPVA (NHPVA) types. Given the variability in pathological features and clinical behavior between the subtypes, evaluating their respective immune microenvironments is essential. They can be categorized into distinct tumor microenvironment immune types (TMIT). Methods: A total of 540 surgically resected ECA samples were classified into HPVA and NHPVA subgroups. Tumor-infiltrating immune markers were assessed using immunohistochemistry. We categorized ECA into four TMIT based on PD-L1 and CD8+ tumor-infiltrating lymphocytes (TILs) expression, and analyzed their prognostic significance. Results: PD-L1 positivity was observed in 319 out of 464 (68.8%) HPVA and 55 out of 76 (72.4%) NHPVA. Across the entire cohort, high CD8+ TILs expression was significantly associated with improved disease-free survival (DFS, p=0.018) and overall survival (OS, p=0.031). A total of 177 samples (32.8%) were classified as TMIT I (high PD-L1 and high CD8+ TILs), exhibiting markedly denser immune cell infiltration compared to the other TMIT groups. In NHPVA subgroup, TMIT was significantly associated with both DFS (p=0.005) and OS (p=0.003). Multivariate analysis identified TMIT as an independent prognostic factor for DFS in the NHPVA group, with TMIT I indicating a more favorable prognosis (p=0.042). Conclusions: TMIT I group within the NHPVA population is most likely to benefit from PD-L1/PD-1 blockade immunotherapies. The immune classification of ECA demonstrates significant prognostic value, suggesting its potential utility in guiding clinical stratification and therapeutic decision-making.